(untitled) (Homoeopathy for All, 2023)
What exercise can do to our body, becomes all the more important in winters, when the cozy cover of warm quilt pushes us towards insidiously injurious sedentary lifestyle (causa occasionalis) which escalate propensity towards gruesome health conditions (constitutional dyscrasias). WHO warns that sedentary lifestyle is a harbinger of various causes of mortality, ushering the ignorant human to a multitude of lifestyle disorders like cardiovascular diseases, diabetes, obesity etc. and heighten the risk of colon cancer, high blood pressure, osteoporosis, lipid disorders, depression and anxiety. According to WHO, 60 to 85% of the world population from both developed as well as developing countries lead sedentary lifestyle. Estimates show that nearly two-third of children are also insufficiently active, which poses serious questions on their future health outcomes.1